Ag(I)/CAAA-Amidphos Complex Catalyzed Asymmetric 1,3-Dipolar Cycloaddition of Acrylates for the Formal Synthesis of (+)-Ibophyllidine - Wang, Haifei; Gong, Chuliang; Zhang, Chen; Zheng, Xiaojun; Hou, Qinglin; Zhou, Qingxia; Zhou, Guiyin; Chen, Yao (Synlett, 2021)
In this work, we introduced a multifunctional Ag(I)/CAAA-amidphos complex catalyzed asymmetric 1,3-dipolar cycloaddition of acrylates with α-imino esters, affording a series of 2,4,5-trisubstituted endo-pyrrolidines in good yields (up to 97%) with high enantioselectivities (up to 98% ee). Meanwhile, the catalytic system was also applied in the three-component one-pot reaction of α-imino esters formed in situ under the action of N,N′-diisopropylcarbodiimide. In addition, the gram-scale reaction was realized for the formal synthesis of (+)-ibophyllidine in eight steps.
Keywords: 1,3-dipolar cycloaddition; α-imino esters; acrylates; three-component; one-pot reaction; (+)-ibophyllidine